A new method to solve and refine algebraic inequalities - DRĂGAN, Marius (Presa Universitară Clujeană, 2025)
In this book the author, teacher Marius Dragan, presents the solving and refinement of some inequalities with higher grade of difficulty. The paperwork is structured in five chapters. The book is one of high standard, with a high level of difficulty and it is mostly addressed to inegalitarians. The majority of the problems also belong to some renowned authors in the field of expertise such as Vasile Cartoaje, Titu Zvonaru, Marian Tetiva, Florin St˘anescu, Marius Dr˘agan, Arkady Alt, Murray Klamkin,Walter Janous, Michael Bataille, Michael Rosenberg etc. The editing was very clear and the solutions are concise but complete.